The Effect of Professional Orientation and Role Conflict on Managerial Performance in Maluku Polda Satker in Maluku - Misa, Ignasius Jaya; Latupapua, Conchita Valentina; Lewaherilla, Novalien Carolina (SEAN Institute, 2024)
The National Police of the Republic of Indonesia, hereinafter abbreviated as POLRI, is a state instrument that plays a role in maintaining public order and security, enforcing the law, and providing protection, protection and service to the community in the context of maintaining domestic security. The method of collecting primary data from respondents was carried out by survey method through distributing questionnaires given to respondents. Survey is a primary data collection method by providing written questions to respondents Respondents in this study were Budget User Authorities (KPA) who worked for the Maluku Regional Police. The research data consisted of 34 questionnaires delivered directly to the respondents who were the object of research. Of the 34 questionnaires sent, all participated in this study because the completed questionnaires were returned in full so they were feasible for analysis in this study.